Exploring Chaos as a Form of Order: A Literary Approach to Gen Z Culture in Angie Thomas’ The Hate U Give - ORKUSA, Ayila (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
As a demographic group, Gen-Z inherits the ‘chaotic’ culture that qualifies as modernism. These Gen-Zers are influencing the world prodigiously. So, our study explores the literary representation of Gen-Z in Angie Thomas’ The Hate U Give with the aim of examining social identity and social justice as part of the major issues in Gen-Z culture. To achieve this, we employ the chaos theory as a theoretical framework to discuss the portrayal of Gen-Z culture in the above literary text. ‘Chaos theory enables us to see the physical world in new ways and to look anew at texts that I call “chaotic”’ (Jo Alyson Parker, 2007). Chaos itself is emblematic of modernism, which encourages continuity and ‘connotes a cultural sensibility rather than a particular period in time’ (Deborah Parsons 2007). Thus, the study of the cultural revolution that Gen-Z represents in literature here follows the thematic issues like police brutality and activism for discussion. The argument is foregrounded on the fact that we are living in a changing world and this change is driven by the media and the internet culture. So Gen-Z’s life in the text is influenced by the social media through internet connectivity. This portrayal is in itself a new order that represents chaos, where youth are depicted as having clarity of self-identity for the purpose of pushing back against unwanted pressure. Even though the youth seem to have lost the battle in the text on the path of pushing back, they still remain hopeful.